Polimorfismos genéticos em pacientes de Goiânia com endometriose: um estudo analítico - Silva, Kleber Santiago Freitas e (2013)
In healthy women, a great number of intra and extracellular controls prevent the attachment and proliferation of ectopic endometrial cells. In endometriosis, abnormalities in those controls can lead to the survival of endometrial cells and consequently their attachment to the peritoneal cavity and disease progression. Endometrial cells with genetic polymorphisms respond to local signals, and they proliferate instead of undergoing apoptosis. The products of these abnormal cells stimulate the invasion of tissues and induce an inflammatory response. The disease has a complex trait and it is related to several factors such as genetic, immunological and environmental. This study examined six polymorphisms presented by six different genes (p53; Estrogen Receptor β; Progesterone receptor; GSTM1; GSTT1; CYP1A1). We obtained the polymorphic genotype frequencies from the same 50 patients for all genes and we analyzed them using the Fisher's Exact Test or G Test. First we analyzed the genes in a group of two and subsequently in a group of three. We found significant association between polymorphisms in six pairs of genes (p53-Erβ with frequency 5.9 times higher in the experimental group; p53-GSTM1, 2.39 times higher; p53-CYP1A1 with 65.5% of the patients with the polymorphism; ERβ-PROGINS 3.0 times higher in the experimental group; GSTM1-PROGINS and GSTT1-CYP1A1 both with 31.25% of the patients with the polymorphism). Positive results were found in 15 situations when genes were analyzed in a group of three; the most significant result corresponding to the polymorphisms of the genes p53, Erβ e GSTM1 with 20% of the patients carrying these polymorphisms; PROGINS, Erβ e GSTM1 with 18% and p53, Erβ e PROGINS with 12%. The results support the idea that the presence of polymorphisms in more than one endometriosis-related gene can lead to the onset of the disease and its progression. Studies should aim at these genes in order to understand the relationship among them more clearly and the possibility of developing new diagnostic techniques based on molecular markers of these genes.